PENGARUH DISPOSIS MATEMATIS DALAM PENDIDIKAN KARAKTER TERHADAP PEMAHAMAN KONSEP KELAS V SEKOLAH DASAR - Feniareny DA (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2017)
Cultural education and character of the nation is basically the development of values that derive from the view of life or ideology of the Indonesian nation. The values in cultural education and character are: religious, honest, tolerant, disciplined, hard work, creative, independent, democracy, curiosity, nationalism, respect for achievement, and communicative. These values correspond to mathematical dispositions in Mathematics learning. This study was aimed at determining: the effect of mathematical disposition in character education toward concept understanding the 5th grade students’ of Elementry School. This study was designed as quasi-experimental research. The data were obtained by using mathematical disposition questionnaires and concept understanding test. Data were analyzed by using t-test. The result of the data showed that there are the effect of mathematical disposition in character education toward concept understanding. Based on calculations obtained t of 3,10 with a significance level of 5% is 1.679.